Clinics and home-based care: the interface between the formal and the informal health sectors - Boros, Adam Kenneth (My University, 2010)
Abstract This paper outlines the findings of a research study designed to explore the working relationship between home-based caregivers and clinic nurses in two informal settlements in Johannesburg, South Africa. In addition, the study focuses on how degrees of informality affect this relationship by including the views and experiences of both sponsored and unsponsored caregivers. The nursecaregiver relationship, which represents one of the primary interfaces between the formal and informal health sectors, is an important part of the country’s primary healthcare system. Despite the focus placed on the integration of HBC into the formal system, very little research has been done examining this link at the ground level. This research aims to help fill this gap. Through a number of qualitative, semi-structured interviews with nurses, caregivers and Department of Health employees, information was collected to gain an understanding of what systems are in place to help facilitate the working relationship and if these systems are helping to create the desired results. Specifically, the study attempts to answer three central questions: What are the primary factors that influence the relationship between HBC organisations and local clinics? How does the degree of informality of these organisations affect this relationship? What are the challenges and the most effective practices related to this partnership? The findings point to a number of both micro-level and macro-level problems with the integration of home-based care into the formal health sector. In addition, degrees of informality are found to have a profound impact on the work of caregivers in some respects, but a surprising lack of impact in others. These issues need to be confronted in order to improve the existing system and, ultimately, health outcomes in South Africa.